2021
DOI: 10.1007/s00395-021-00898-0
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of STAT3 and its role in cardioprotection by conditioning: focus on non-genomic roles targeting mitochondrial function

Abstract: Ischemia–reperfusion injury (IRI) is one of the biggest challenges for cardiovascular researchers given the huge death toll caused by myocardial ischemic disease. Cardioprotective conditioning strategies, namely pre- and post-conditioning maneuvers, represent the most important strategies for stimulating pro-survival pathways essential to preserve cardiac health. Conditioning maneuvers have proved to be fundamental for the knowledge of the molecular basis of both IRI and cardioprotection. Among this evidence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 249 publications
(396 reference statements)
1
27
0
Order By: Relevance
“…Stat3 has become a research hotspot because of its essential function during diverse biological processes such as proliferation, differentiation, anti-apoptosis, inflammatory response, and angiogenesis ( Cheng et al, 2020 ; Tian et al, 2020 ; He et al, 2021 ). In previous researches, Stat3 was considered as a critical signaling molecule for immune escape, atherosclerosis, malignancy and cardiac injury ( Huynh et al, 2017 ; Chen et al, 2019 ; Comita et al, 2021 ; Zhang et al, 2022 ). Over-activation of Stat3 will lead to poor prognosis and drug resistance in osteosarcoma ( Liu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Stat3 has become a research hotspot because of its essential function during diverse biological processes such as proliferation, differentiation, anti-apoptosis, inflammatory response, and angiogenesis ( Cheng et al, 2020 ; Tian et al, 2020 ; He et al, 2021 ). In previous researches, Stat3 was considered as a critical signaling molecule for immune escape, atherosclerosis, malignancy and cardiac injury ( Huynh et al, 2017 ; Chen et al, 2019 ; Comita et al, 2021 ; Zhang et al, 2022 ). Over-activation of Stat3 will lead to poor prognosis and drug resistance in osteosarcoma ( Liu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The SAFE pathway, including the signal transducer and transcription activator (STAT)-3 and STAT5, and the RISK pathway, including PI3K/Akt, can play a central role in RIC cardioprotection—in both humans and mice [ 20 ]. Indeed, in STAT5 knockout mice it was found that RIC-induced infarct size reduction occurs via the PI3K/Akt pathway and the anti-apoptotic cascade, thus confirming the importance of RISK in rodents [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cardioprotective conditioning strategies are strategies for activating prosurvival pathways and keep cardiac health. Signal transducer and activator of transcription 3 (STAT3) are not only the transcription factors but also exhibit nongenomic prosurvival functions preserving mitochondrial function from I/R injury [ 87 ]. It has been reported that the activity of MCU could be influenced by STAT3 [ 88 ].…”
Section: Mitochondrial Damage In Ischemia/reperfusion Injurymentioning
confidence: 99%